The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1136/ard.60.2.112
|View full text |Cite
|
Sign up to set email alerts
|

UVA-1 cold light treatment of SLE: a double blind, placebo controlled crossover trial

Abstract: Objective-Treatment of patients with systemic lupus erythematosus (SLE) often implies strong drugs with possibly serious side eVects. Thus there is a need for new immunosuppressive treatments. Long wave ultraviolet A (UVA-1) cold light therapy is an anti-inflammatory, immunomodulatory treatment with a possible systemic eVect and few side eVects. In the current study low dose UVA-1 cold light treatment was tested to determine whether it reduces disease activity in SLE. Methods-Eleven patients with SLE were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 11 publications
0
32
0
2
Order By: Relevance
“…Both, scleroderma and lupus erythematosus respond well to low- or medium-dose UVA1 phototherapy [2, 3, 4, 5, 6, 7]. In our case displaying clinical features of both entities, we used a treatment schedule suggested by Sönnichsen et al [4]for subacute cutaneous lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both, scleroderma and lupus erythematosus respond well to low- or medium-dose UVA1 phototherapy [2, 3, 4, 5, 6, 7]. In our case displaying clinical features of both entities, we used a treatment schedule suggested by Sönnichsen et al [4]for subacute cutaneous lupus erythematosus.…”
Section: Discussionmentioning
confidence: 99%
“…We report here on a boy who had CD4+ cell microchimerism with maternal cells and who presented himself with a severe chronic progressive skin disease with clinical and histological features similar to features of chronic graft-versus-host disease. Since his skin did not respond well to systemic immunosuppressive drugs including prednisolone, azathioprine, cyclosporine A and mycophenolate mofetil alone, we decided to treat with UVA1 phototherapy which has been shown to improve scleroderma [2, 3], lupus erythematosus [4, 5, 6, 7]and chronic graft-versus-host disease [8]. We report here on the good clinical effect of this treatment on his skin involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Its use has lately been documented mainly in atopic dermatitis [6,7,8], localized scleroderma [9,10] and in lichenoid dermatosis [11]. Other diseases responding to UVA1 phototherapy include keloids [12], urticaria pigmentosa [13] and systemic lupus erythematosus [14]. The value of using UVA1 in the treatment of cutaneous lymphomas has also been qualified by several authors [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…56 In another published double-blind, placebocontrolled (visible light), crossover study, which was performed in 11 patients with SLE in two consecutive 1-week periods, it was strongly suggested that low-dose UVA1 treatment reduces disease activity. 57 Recently, UV-hardening therapy was claimed as a novel intervention in patients with photosensitive CLE. In a retrospective study of continuous, homebased, UVB hardening therapy, 44 patients with confirmed photosensitivity and cutaneous manifestations of LE were included (9 SLE, 21 DLE, 10 SCLE, 4 not-specified CLE).…”
Section: Uva1 Therapymentioning
confidence: 99%